THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP IN EMPLOYEE CAREER DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW - Fitriadi, Ahmad; Dumayanti Sihombing, Sabar; Fernando Simatupang, Leo; Bherna D Nainggolan, Anju; Berlien, Richard (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
In today’s dynamic work environment, leadership plays a critical role in shaping employee career trajectories. This systematic literature review (SLR) examines the influence of transformational leadership (TL) on employee career development by synthesizing 48 peer-reviewed studies published between 2022 and 2025. Guided by the PRISMA methodology, this review draws on three key theoretical frameworks—Transformational Leadership Theory, Social Cognitive Career Theory (SCCT), and Leader–Member Exchange (LMX) Theory—to explore the behavioral, psychological, and relational mechanisms that underpin this relationship. Findings reveal a consistent positive association between TL and various career development outcomes, including career satisfaction, employability, adaptability, and goal clarity. Mediating variables such as self-efficacy, work engagement, and career adaptability were commonly identified, while organizational culture, industry type, and demographic factors served as key moderators. The review also highlights a strong reliance on cross-sectional methodologies and a limited number of studies in non-Western contexts, indicating important gaps in the current literature. This paper concludes that transformational leadership fosters a supportive environment for employee growth by enhancing motivation, providing individualized guidance, and strengthening relational trust. However, future research is needed to develop longitudinal and culturally inclusive models that better capture the complexity of leadership’s role in career development. The review offers practical implications for organizations seeking to align leadership development with career management strategies to attract, retain, and empower talent in an increasingly competitive landscape.